Abstract Number ‐ 190: Acute Ischemic Stroke patients post Endovascular Thrombectomy complicated by gastrointestinal bleeding have worst clinical outcomes - Syed F Ali; Jose Dominguez; Masha Osman; Sarah Meadows; Ankita Das; Fawas Al‐Mufti (Stroke: Vascular and Interventional Neurology, 2023)
Introduction The objective of this study was to scrutinize the stroke severity markers, complications, and clinical outcomes in patients with AIS who underwent EVT complicated by gastrointestinal bleeding (GIB). It is known that anemia is associated with poor functional outcomes in patients with mechanical thrombectomy (Nisar, 2021). Anemia also predicts poor clinical outcomes despite fair or good collateral circulation (Pienimäki, 2020). With the increasing use of EVT for acute management of AIS, it is prudent to investigate the relationship between gastrointestinal bleeding in acute ischemic stroke patients who have underwent mechanical thrombectomy. Methods The 2016–2019 National Inpatient Sample (NIS) database was queried for patients with the diagnosis of acute ischemic stroke (AIS) by using International Classification of Disease, 10threvision (ICD10) diagnosis codes. From this cohort of AIS patients, those that underwent endovascular thrombectomy (EVT) were then identified using ICD 10 procedure codes. A subpopulation of AIS‐EVT patients was created for patients with a diagnosis of GI bleeds. Baseline demographic, stroke severity, complication, and outcome variables were evaluated between GI bleed and no‐GI bleed patients who underwent EVT. Results Of 132,210 patients hospitalized for AIS who had underwent EVT, there were 130,970 cases of no GIB (99.1% %) and 1,240 cases of GIB (0.9%) complications. Mean age greater than 65 was 980 (79%) in GI bleed group versus 82,945 (63.3%) in no GI bleed group (p‐value < 0.001, CI 95%: 1.903 ‐ 2.5, OR 2.2). Interestingly, the no GI bleed group had more use of Aspirin 31,790 (24.3%) versus GI bleed group 200 (16.1%) (p‐value < 0.001, CI 95%: 0.515 ‐ 0.698, OR 0.6). Furthermore, the GI bleed group had the following risk factors that were statistically significant: history of atrial fibrillation and chronic renal failure (46% vs 37.2% and 21.8% vs 15.1%, respectively). In fact, this study failed to show increased risk of GI bleed due to being on aspirin, AC, having a history of DM, HTN, HLD, and CHF. Stroke severity was worst in GI bleed group with average NIHSS score 15.92 vs 14.05 (P‐value < 0.001) and worst hemiplegia (75% vs 70.2%, P‐value < 0.001, 1.3 CI 1.118‐1.447). The GI bleed group had statistically worst complications including sepsis, DVT, PE, AKI, and aspiration pneumonia. Lastly, the GI bleed patients were most likely to be discharged to SNF versus routine discharge to home (68.5% vs 49.6%, p‐value < 0.001, CI 1,962 ‐ 2.496, OR 2.2). Conclusions GIB occurrence in patients with AIS status post EVT is relatively rare but is associated with poor in‐hospital outcomes, including mortality. We identified risk factors associated with GIB in AIS post EVT, which allows physicians to monitor patient populations at the highest risk.